Estudo comparativo entre dois adesivos no desempenho mastigatório de usuários de próteses totais - Oliveira Junior, Norberto Martins de [UNESP] (2014)
Objective: The objective of this study was evaluate the effect of use of two denture adhesives in relation to masticatory performance of conventional complete denture wearers, by means of a cross-over study. Material and Method: Fifty edentulous individuals received new bimaxillary complete dentures and, after the adaptation period, were submitted to masticatory performance analysis with complete dentures without adhesives (control). So, the sample was randomly divided and assigned to two protocols, in which the adhesives order of use was different. The adhesives Ultra Corega cream and Ultra Corega powder were used for 15 days prior the application of new masticatory performance analysis, by all the sample, and respecting a washout period, also 15 days, between the use of each adhesive. The masticatory performance was evaluated by sieves method. Data were analyzed by nonparametric Friedman test and multiple comparison of average orders using test DUNN (α=.05). Results: There was significant increase in masticatory performance after use of adhesives Ultra Corega cream (med=27.4%) and Ultra Corega powder (med=28.0%), when these were compared to the control group (med=16.5%) (p<.001; n=30), without statistically significant difference between the tested adhesives (p=0,897; n=30). Conclusions: The use of adhesives increased masticatory performance of conventional complete denture wearers, and there was no difference for masticatory performance as the use of adhesives in the forms of cream and powder.